Molecular Simulation of Gas Solubility in Nitrile Butadiene Rubber. - Khawaja,M; Sutton,AP; Mostofi,AA (J Phys Chem B, 2017)
Molecular simulation is used to compute the solubility of small gases in nitrile butadiene rubber (NBR) with a Widom particle-insertion technique biased by local free volume. The convergence of the method is examined as a function of the number of snapshots upon which the insertions are performed and the number of insertions per snapshot and is compared to the convergence of the unbiased Widom insertion technique. The effect of varying the definition of local free volume is also investigated. The acrylonitrile content of the polymer is altered to examine its influence on the solubility of helium, CO2, and H2O, and the solubilities of polar gases are found to be enhanced relative to those of nonpolar gases, in qualitative agreement with experiment. To probe this phenomenon further, the solubilities are decomposed into contributions from the neighborhoods of different atoms, using a Voronoi cell construction, and a strong bias is found for CO2 and H2O in particular to be situated near nitrogen sites in the elastomer. Temperature is shown to suppress the solubility of CO2 and H2O but to increase that of helium. Increasing pressure is found to suppress the solubility of all gases but at different rates, according to a balance between their molecular sizes and electrostatic interactions with the polymer. These results are relevant to the use of NBR seals at elevated temperatures and pressures, such as in oil and gas wells.